Observational Research in Homeopathy: Improving Homoeoprophylaxis Research Outcomes - Golden, Isaac (Homœopathic Links, 2018)
Introduction We now have a substantial evidence base supporting the effectiveness of homoeoprophylaxis (HP), but the quality of the evidence is variable. Most interventions are not controlled clinical studies but are undertaken in emergency situations to prevent loss of life and suffering using observational methodology. Methods are developed to improve the quality of future observational research into H2, with consequences for general homeopathic research.Methods Different methods used to improve the quality of research were considered, and their ability to improve the quality of HP research was considered.Results Randomised controlled trials (RCTs) are often not the most appropriate method to use in HP research. Observational methods are mostly suitable to study HP interventions. There are a range of techniques which can be used to improve the quality of observational research. A Homoeoprophylaxis Research Checklist is prepared for consideration.Discussion Prospective observational studies will often provide a more relevant research framework. Research techniques to improve research quality need to be incorporated in future HP interventions to allow meaningful results to be produced.Conclusion The use of appropriate homoeoprophylaxis programs to prevent targeted infectious diseases has an established place in homeopathy. Its ability to produce a significant and consistent level of protection has been shown time and again in large HP interventions conducted by practitioners, usually with orthodox medical training. More and better-quality research will continue to strengthen the evidence-based case for the use of HP both in short- and long-term infectious disease prevention. Using a standardised research checklist should help improve the quality of research into HP in the future.
Keywords: homoeoprophylaxis; observational research; homoeoprophylaxis research checklist